Hak Asasi Manusia Dalam Perspektif Islam - Leila Setia Ningsih; Suci Wahyu Tami Br Rambe; Rizki Mahyani Br Hasibuan,; Afriadi Amin; Abdul Karim Batubara (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The research entitled Human Rights in an Islamic Perspective seeks to reveal human rights in the context of Islamic perceptions in the era of Islamic research, as well as what perceptions humans face when exercising human rights. Descriptive qualitative research method was used. According to the research findings, human rights in Islamic perception include the following things: glorifying and providing maximum protection, so that human existence is fully maintained and protected, as well as the realization of public and individual interests based on a balance of rights and obligations. In Islam, human rights are determined transcendentally for the benefit of the people through Islamic law which is revealed through revelation. As sources of Islamic law, the Al-Qur'an and As-Sunnah uphold human rights. Long before the world community thought about it, the Qur'an has established the principles of human rights, truth and justice as the main source of law for Muslims, and the protection of human rights in Islam, including: (1) the right to life, (2) right to freedom of religion, (3) right to justice, (4) right to equality, (5) right to education, (6) right to freedom of expression, and (7) property right. . Keywords: human right, Islamic perception